Banana21: From Gene Discovery to Deregulated Golden Bananas - Paul, Jean-Yves; Harding, Robert; Tushemereirwe, Wilberforce; Dale, James (Frontiers in Plant Science, 2018)
Uganda is a tropical country with a population in excess of 30 million, more than 80% of whom live in rural areas. Bananas (Musa spp.) are the staple food of Uganda with the East African Highland banana (EAHB), a cooking banana, the primary starch source. Unfortunately, these bananas are low in pro-vitamin A (PVA) and iron and, as a result, banana-based diets are low in these micronutrients which results in very high levels of inadequate nutrition. This inadequate nutrition manifests as high levels of vitamin A deficiency (VAD), iron deficiency anaemia and stunting in children. A project known as Banana21 commenced in 2005 to alleviate micronutrient deficiencies in Uganda and surrounding countries through the generation of farmer- and consumer-acceptable edible bananas with significantly increased fruit levels of PVA and iron. A genetic modification approach was adopted since bananas are recalcitrant to conventional breeding. In this review, we focus on the PVA-biofortification component of the Banana21 project and describe the proof-of-concept studies conducted in Australia, the transfer of the technology to our Ugandan collaborators and the successful implementation of the strategy into the field in Uganda. The many challenges encountered and the potential future obstacles to the practical exploitation of PVA-enhanced bananas in Uganda are discussed.